2015
DOI: 10.1176/appi.ps.201400206
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Predictors of Clinic Adoption of State-Supported Trainings in Children’s Services

Abstract: Objective Characteristics associated with participation in training in evidence-informed business and clinical practices by 346 outpatient mental health clinics licensed to treat youths in New York State were examined. Methods Clinic characteristics extracted from state administrative data were used as proxies for variables that have been linked with adoption of innovation (extraorganizational factors, agency factors, clinic provider-level profiles, and clinic client-level profiles). Multiple logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In an earlier study with the entire cohort of mental health clinics in New York State from which this sample was drawn, Olin et al [29] found clinic size, efficiency and outsourcing were significantly associated with participation in business trainings and proportion of youth clients and full-time clinical staff were associated with participation in clinical trainings. The present study enriches those findings by highlighting the potential importance of local/contextual factors not available in state administrative data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study with the entire cohort of mental health clinics in New York State from which this sample was drawn, Olin et al [29] found clinic size, efficiency and outsourcing were significantly associated with participation in business trainings and proportion of youth clients and full-time clinical staff were associated with participation in clinical trainings. The present study enriches those findings by highlighting the potential importance of local/contextual factors not available in state administrative data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior work, we found that larger clinical staff capacity and having a higher proportion of youth clients predicted participation in state-supported evidence-based practice training. 23 Having a larger clinical staff capacity may explain the shorter psychiatry appointment wait times in these clinics. However, in our model, clinical staff capacity (i.e., clinical fulltime equivalent) was not significantly associated with psychiatry wait times.…”
Section: Discussionmentioning
confidence: 99%
“…22-23 Briefly, clinics were characterized by OMH-defined administrative regions (Central, Hudson, Long Island, NYC, Western) and clinic types (hospital, state-operated facilities vs. community clinics). Data from the US Department of Health and Human Services Area Health Resources Files (AHRF) provided county rural–urban continuum codes that were used to categorize clinics by urbanicity (metropolitan versus non-metropolitan).…”
Section: Methodsmentioning
confidence: 99%
“…Questions were adapted from ongoing research with New York State behavioral health agencies (Chor et al, 2014; Chor, Wisdom, Olin, Hoagwood, & Horwitz, 2015; Olin et al, 2015a, 2015b). The in-person interviews asked about barriers and facilitators to implementing and sustaining services, current and future needs of the community, local professional networks, and characteristics of an ideal services system.…”
Section: Methodsmentioning
confidence: 99%